A Sociological Analysis of Hustle Culture Among Generation Z in the Philippine Gig Economy - Rubenito Barrot Rubenito Barrot; Mary Dionisio-Sese; Anna Mae Gomez (International Journal of Humanities, Management and Social Science (IJ-HuMaSS), 2026)
Hustle culture the systemic glorification of overworking and continuous multi-tasking has rapidly emerged as a dominant socio-behavioral norm among Generation Z in the Philippines. Driven by hyper-connectivity, the proliferation of digital gig platforms, and persistent macroeconomic inflation, the younger demographic has increasingly internalized productivity as a measure of self-worth. This study examines the socio-economic drivers of hustle culture among Filipino Gen Z and analyzes its subsequent ramifications on mental well-being and labor market retention. Utilizing a qualitative-descriptive approach grounded in contemporary social-exchange and structural-functionalist theories, this paper reveals that while hustle culture is framed as a vehicle for upward mobility, it fundamentally operates as a structural survival mechanism. This mechanism induces chronic burnout, psycho-emotional exhaustion, and counter-movements such as “quiet quitting.” The study concludes with institutional recommendations for human resource management and public policy to foster sustainable workforce practices.